2020
DOI: 10.18203/2319-2003.ijbcp20204500
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics usage, how well we know it? KAP survey among the dentist population in Mumbai

Abstract: Background: There is a rising concern for antibiotic resistance worldwide, the primary cause of which is overuse and misuse. This study primarily aimed at assessing the knowledge of dental practitioners regarding the current guidelines on use of antibiotics and to identify the shortcomings if any.Methods: Present study was a cross-sectional questionnaire-based study conducted amongst 450 dental practitioners across Mumbai with the help of a self-designed questionnaire. The data was entered into excel sheets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Studies conducted by Amisha et al 2020 and Singh et al found that <40% of dentists have advised antibiotic culture test, and in this study, only 15.3% of dentists have advised it [ 21 , 22 ]. Furthermore, about 61.4% of patients have self-prescribed antibiotics, and 50% of patients haven’t responded to the antibiotics which is almost similar to the results of the study done by Amisha et al This provides us the hint that we should focus on antibiotic culture tests.…”
Section: Discussionmentioning
confidence: 59%
“…Studies conducted by Amisha et al 2020 and Singh et al found that <40% of dentists have advised antibiotic culture test, and in this study, only 15.3% of dentists have advised it [ 21 , 22 ]. Furthermore, about 61.4% of patients have self-prescribed antibiotics, and 50% of patients haven’t responded to the antibiotics which is almost similar to the results of the study done by Amisha et al This provides us the hint that we should focus on antibiotic culture tests.…”
Section: Discussionmentioning
confidence: 59%
“…SRB/SDC/PhD/OPATH-2114/23/117). Following approval, a semi-structured questionnaire was prepared and shared via Google Forms (Alphabet Inc., Mountain View, CA, USA) following a review of existing literature on the topic [ 3 , 11 , 15 , 17 , 18 ]. The survey was conducted between January 2023 and July 2023, involving dental practitioners in Hyderabad (Telangana, India).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was designed to ensure that the questions were well-informed, comprehensive, and as per the purpose of this study. Some questions were designed after discussion among the authors, and some were referred to from the previous literature by Parekh et al [ 3 ] and Aragoneses et al [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have highlighted concerns regarding the prescription of antibiotics by dentists, particularly in relation to the growing problem of antibiotic resistance (1). Health organizations globally have intensified their focus on the judicious use of antibiotics (2)(3)(4). In the realm of dental practice, antibiotics are essential for treating various infections.…”
Section: Introductionmentioning
confidence: 99%